Up From Slavery - Washington, Booker T. (Saga Egmont, 2022)
For those interested in the history of slavery and the American Civil War, \'Up from Slavery\' is the autobiography from American eudcator Booker T. Washington in which he describes his experiences of living as an enslaved child during the Civil War. Washington overcame many obstacles to get an education and throughout his autobiography, he gratefully reflects on the help of his teachers and philanthropists who helped educate Black and Native Americans.The autobiography was a best seller; much to do with its honest and historically significant depiction of the struggles that Washington faced. If you are eager to know more about the history of slavery, Sojourner Truth\'s \'Narrative of Sojourner Truth\' will provide great insight into being a slave in the North. -